La transformación del bosque seco desde la mirada geográfico-ambiental, en la Cuenca hidrográfica del río César (2017)
In Colombia, the demographic impact that had the colonization, the introduction of cattle in the mid seventeenth century and the uncontrolled expansion of the agricultural frontier, have been converted to the dry forest in the most threatened ecosystem of our country (Bermúdez, 2011); the majority of studies concerning the transformation of this type of vegetation, unknown causes, focusing on the object (the coverage changes); the present research investigates the geographic-environmental variables influencing the process of modification of the dry forest, exactly in the watershed of the Cesar river (northern Colombia), one of the regions with greater coverage of the ecosystem now (Pizano & García, 2014). Mapping the space-temporal evolution and determine the reasons by which turned the vegetation of the biome, is of great importance, since being generated inputs for the recovery and protection of the dry forest, at the same time ensures the conservation of the goods and services that it offers. In addition, it can be a tool to mitigate problems such as desertification; for example, in Colombia it is reported that more than half of the original area of the ecosystem has degraded to this point (García, Corzo, Isaacs & Etter, 2014). In terms of methodology, geographic information systems (GIS) and remote sensing were included; two techniques allowed to determine the coverages for which the dry forest was replaced, based on a multitemporal analysis (years 1986 and 2015). In addition, the five environmental components (atmospheric, hydrospheric, geospheric, biospheric and antropospheric) for the entire basin; in order to establish the relationship between changes in each ecosystem. The results show that in the year 2015, coverage of dry forest, had decreased by 70,40% over what existed in 1986, this is because the climatic conditions (atmospheric component), the fertility of the soil (geosferic) and the very structure of the ecosystem (biospheric), match the characteristics that sought and still looking for humans to settle and facilitate the development of the populations (antropospheric) (Galvis & Mesa, 2014). Finally, it was concluded that the processes of planning and territorial ordering (local and regional level), do not recognize the geographic-environmental variables that have caused the transformation of the ecosystem, and much less have fulfilled their objective of reducing the phenomenon.